A founder RDH5 splice site mutation leads to retinitis punctata albescens in two inbred Pakistani kindreds. (2nd January 2020) - Khan, Rizwan; Shabbir, Rana Muhammad Kamran; Raza, Irum; Abdullah, Umair; Naeem, Muhammad Asif; Ahmed, Ashfaque; Malik, Sajid; Hu, Zhengmao; Xia, Kun
ABSTRACT: Background : Retinitis punctate albescens (RPA) is a rare form of retinal dystrophy characterized by congenital stationary night blindness and a characteristic fundus appearance. Missense or nonsense mutations in RDH5 in homozygous or heterozygous state have been implicated in RPA . Material and methods : Two consanguineous Pakistani kindreds with the highly variable manifestation of RPA were studied. Whole-exome sequencing was applied to the index subjects in both families. Sanger sequencing of the candidate RDH5 variant was carried out. Pathogenicity of the detected variant was assessed through bioinformatics tools. Results : The ophthalmic examination through full-field electroretinogram of affected patients in both families was consistent with RPA. A novel splice donor variant at the first exon/intron boundary of RDH5 (NM_002905.3: c.-33 + 2dup) segregated in recessive fashion with the clinical phenotype in both families. One of the heterozygous variant carriers was also observed to have a milder expression of retinal flecks. Haplotype analysis surrounding the splice variant and pattern of runs of homozygosity were suggestive of common ancestry in these families. Conclusion : This is the first report of any pathogenic splice variant at first exon/intron boundary implicated in RPA and suggests another mechanism through which RDH5 variants could be associated with eye phenotype. This study also highlights the importance of a thorough phenotypic evaluation of heterozygous mutation carriers who may exhibit milder symptoms.